Automatic creation of massive virtual cities - Poullis, Charalambos; You, Suya (My University, 2009)
This research effort focuses on the historically-difficult problem of creating large-scale (city size) scene models from sensor data, including rapid extraction and modeling of geometry models. The solution to this problem is sought in the development of a novel modeling system with a fully automatic technique for the extraction of polygonal 3D models from LiDAR (Light Detection And Ranging) data. The result is an accurate 3D model representation of the real-world as shown in Figure 1. We present and evaluate experimental results of our approach for the automatic reconstruction of large U.S. cities.
Keywords: Imaging, Three-Dimensional; Optical radar; Virtual reality